Limiting amino acids for growing cattle fed diets based on soybean hulls - Greenwood, H.; Löest, C.A.; Titgemeyer, Evan C. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Ruminally cannulated Holstein steers were used in three nitrogen balance experiments to determine the sequence of limiting amino acids for growing steers fed soybean hull-based diets. The steers in all experiments were fed the same basal diet (73% soybean hulls, 19% alfalfa, DM basis; formulated to minimize rumen undegradable intake protein and thus maximize microbial protein postruminally) and were given the same intraruminal infusions (400 grams per day acetate; to increase energy supply without increasing microbial protein supply). In experiment 1, treatments consisted of abomasal infusions of: water (control, no amino acids); Lmethionine; and a mixture of 10 essential amino acids. Nitrogen retention (a measure of protein deposition) was greatest for steers receiving the mixture, and steers receiving methionine alone had greater nitrogen retention than control steers. In experiment 2, treatments consisted of abomasal infusions of the mixture of 10 essential amino acids or the same mixture without lysine. Nitrogen retention tended to be greater for the 10 amino acid mixture than for the mixture without lysine. In experiment 3, threonine, rather than lysine, was removed from the amino acid mixture. Nitrogen retention was not affected by removal of threonine. We conclude that methionine was the first limiting amino acid, threonine was not limiting, lysine appeared to be a limiting amino acid, and one or more untested amino acids in the mixture appeared to be second most limiting. Therefore, our data do not support the generally accepted concept that the sequence of limiting amino acids for steers is methionine, lysine, and threonine when microbial protein is the primary contributor to metabolizable (postruminal) protein.
Keywords: Beef; Steers; Requirements; Amino acids; Nitrogen balance; Soybean hulls